A MEKANISME PENETAPAN HARGA DALAM PANDANGAN AL-GHAZALI (STUDI PADA PEDAGANG SAYUR PASAR PANORAMA BENGKULU) - Saputra, Ahmad Lio (JSE: Jurnal Sharia Economica, 2025)
This study is motivated by the importance of fair pricing in Islamic economics as emphasized by Al-Ghazali, who highlights honesty, transparency, and balance in market transactions. The research aims to explore the implementation of Al-Ghazali’s concept of fair price in trading practices at Panorama Market, Bengkulu. This study employs a qualitative method with a phenomenological approach through in-depth interviews with six traders and two buyers, as well as direct observation of market activities. The findings reveal that most traders at Panorama Market apply fair pricing principles in line with Al-Ghazali’s concept, although certain practices are still influenced by market conditions and short-term profit motives. The study concludes that Al-Ghazali’s perspective remains relevant in traditional market contexts, particularly in maintaining transaction blessings and preventing price injustice.